Implementasi Pendidikan Karakter dalam Pembentukan Karakter Disiplin Beribadah Karyawan di Rumah Makan 1 Sambel Layah Purwokerto - Abdiyah, Khusnul (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2020)
Character education is the shaping of personality based on certain beliefs, either individually or in a group. There are 18 characters education according to DIKNAS, one of it is discipline character. There are three kinds of discipline character, one of it is the discipline character of worship. The study was focused on one of the character education that is the character of worship discipline. The purpose of this study for knowing the implementation of character education in the development of the discipline character of religious workers at the restaurant 1 sambel Layah Purwokerto. This research is fieldresearch or field research, the method of this research is qualitative, which the data-collection techniques used observation, interviews, and documentation. Based on analysis ,the religious activity carried out at the 1 sambel layah purwokerto dinner for employees. The implementation of the character education of the discipline of worship. The nature of the activity included worshipers, shesters, reading of the Koran, memorized and regular exposition. The formation of a disciplined character is expected to make an employee at the restaurant 1 sambel layah should be able to make an employee a good character, quality and balance between the ingredients of live in the world and the hereafter.